Contextual Physics Learning Based on Geothermal Areas to Improve Scientific Literacy and Scientific Communication Skills - Salman Hamja Siombone; Fitri Ayu Lestari; Wiyono Wiyono (Jurnal Pendidikan MIPA, 2024)
This study aims to develop a learning physics module through contextual learning design based on geothermal areas to improve scientific literacy ability and scientific communication skills on temperature and heat concepts. The sample in this study was 27 respondents of Mathematics Education STKIP Gotong Royong Masohi who are taking general physics subjects. The method used in this study is educational design research with the Plomp & Nieveen development model. The main instrument developed in this study is a prototype of a contextual physics learning module. The average percentage value of the validation results of the contextual physics learning module (prototype-1) from three experts on content (substance), language, and construct aspects is 88.41%, which shows that it is in the very valid category. The results of the trial of the practicality of the learning module in the one-to-one test obtained an average percentage value of 95.45%, and the results of the limited class trial (small group) received an average percentage value of 95.88%, which shows that the learning module developed is very practical. The results of the student's scientific literacy competency test at the field test (large class) showed an increase with an average N-gain of 0.75, which is in the high category; these results indicate that the learning physics module developed has been effective. The results of implementing the contextual physics learning module (prototype-2) in the field showed that students' average total scientific communication skills increased from 90.95 at the first meeting to 92.85 at the second meeting. Based on the results of the data analysis obtained, it can be concluded that the contextual physics learning module developed has met the valid, practical, and effective categories and can increase scientific literacy and scientific communication skills so that they are suitable for use in the learning process in the field.         Keywords: contextual physics learning, geothermal area, educational design research, science literacy and scientific comunication skills.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp986-1011